The standards of obstetrics and gynecology core outcome sets: A scoping review - Jiyuan Shi; Ya Gao; Shuang Wu; MingMing Niu; Yamin Chen; Meili Yan; Ziwei Song; Hui Feng; Junhua Zhang; Jinhui Tian (Integrative Medicine Research, 2022)
Background: Core outcome sets (COSs) are the minimum outcomes which should be measured and reported by researchers investigating a specific condition. The definition of standards of COSs vary across different health-related areas. This investigated the characteristics of COSs regarding obstetrics and gynecology (OG) and examined the reports and designs of standards of OG COSs. Methods: A comprehensive search was conduced on the COMET database on December 20, 2019 to identify systematic reviews on COSs. Two reviewers independently evaluated whether the reported OG COS met the reporting requirements as stipulated in the Core Outcome Set-STAndards for Reporting (COS-STAR) statement checklist and the minimum design recommendations as outlined in the Core Outcome Set-STAndards for Development (COS-STAD) checklist. Results: Forty-four OG COSs related to 26 topics were identified. None of them met all the 25 standards of COS-STAR statement which representing 18 items considered essential for transparent and complete reporting list for all COS studies (range: 6.0-24.0, median: 14.0). The compliance rates to 16 standards of methods and result sections ranged from 27.3%–68.2%. Total COS-STAR compliance items for OG COSs with the prior protocol was significantly higher than without prior protocol (MD = 3.846, 95% CI: 0.835–6.858, P = 0.012). None of the OG COSs met all the 12 criteria in the COS-STAD minimum standards (range: 3.0-11.0, median: 5.0). The compliance rates for all three standards of stakeholders involved and all four standards of the consensus process were lower than 60%. Conclusions: Methodological and reporting standards of OG COSs should be improved.